Enzymatic Synthesis of Citronellyl Palmitate in Organic Media: Process Optimization and Kinetic Evaluation - Rashid, Ayoub; Virk, Naeem Akhtar; Sadiq Butt, Abdul Rehman; Adnan, Ahmad; Pervaiz, Muhammad; Raza, Muhammad Arshad; Syed, Quratulain (Asian Journal of Chemistry, 2015)
Kinetics of citronellyl palmitate ester formation from citronellol-palmitic acid was studied by using immobilized lipase Novozym 435 Candida antarctica. Lipase immobilized onto macroporous acrylic resin gave the best results. Different parameters like reaction medium, temperature, substrate concentration were optimized for the enzymatic synthesis of citronellyl palmitate. The optimum temperature was 30 °C, optimum molar ratio of alcohol to acid was 1:1. The best solvent for maximum esterification was n-hexane. At higher concentration of alcohol enzyme inhibition took place.